STRATEGI KOMUNIKASI BISNIS HIPMIKINDO DALAM MENSINERGIKAN SUMBERDAYA AKADEMISI DAN PELAKU UMKM - Misnan Misnan; Rezzi Nanda Nanda Barizki (Universitas Prof. Dr. Moestopo (Beragama), 2021)
The synergy of MSME actors and academics is a new thing in facing the challenges of digitalization. HIPMIKINDO has a strategic positioning between the two parties. The purpose of this research is to know the business communication strategy of HIPMIKINDO in synergizing the resources of academics and SMEs. Through qualitative approach and descriptive method, the result obtained is the form of the terminology concepts of the business communication strategy of pull, push and pass. In the push business communication strategy, HIPMIKINDO implements the managing business disruption message, which is exist a threat to MSME business continuity, so that the context of entrepreneurship requires transformative acceleration towards technopreneurship. At the push step, the motivation of the business cycle without innovation and creativity must be faced with resource competencies. This can be overcome by the presence of the role of academics in accelerating the development of MSME capacity building. Furthermore, the pass is implemented with the establishment of an entrepreneur center, which becomes a communication node for academics, MSMEs as well as across parties and institutions that want to play more active in synergies.